Examination of The Ocular Tolerability of Topical Fixed Combinations Drug Treatments In Patients With Primary Open-Angle Glaucoma (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the ocular tolerability of topical drug treatments of brimonide tartrate-timolol maleate, dorzolamid hydrochloride-timolol maleate and latanoprost-timolol maleate in patients with primary open angle glaucoma.
Keywords: s: Brimonidin; Dorzolamid; Latanoprost; Primary Open Angle Glaucoma; Ocular Discomfort Scala; Timolol; Ocular Tolerability.